The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/bdi.12885
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructure in youth with and at risk for bipolar disorder

Abstract: Objectives Bipolar disorder (BD) and familial risk for BD have been associated with aberrant white matter (WM) microstructure in the corpus callosum and fronto‐limbic pathways. These abnormalities might constitute trait or state marker and have been suggested to result from aberrant maturation and to relate to difficulties in emotion regulation. Methods To determine whether WM alterations represent a trait, disease or resilience marker, we compared youth at risk for BD (n = 36 first‐degree relatives, REL) to y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…Global or regional white matter disruptions have consistently been reported in BD patients, both recently diagnosed, 49 patients with longer duration of illness 80 and young first‐degree relatives of patients with BD 81,82 . Our demonstration of lower cerebral white matter volume in CI patients extends previous findings by suggesting these deficits may be specific to cognitively impaired patients.…”
Section: Discussionsupporting
confidence: 83%
“…Global or regional white matter disruptions have consistently been reported in BD patients, both recently diagnosed, 49 patients with longer duration of illness 80 and young first‐degree relatives of patients with BD 81,82 . Our demonstration of lower cerebral white matter volume in CI patients extends previous findings by suggesting these deficits may be specific to cognitively impaired patients.…”
Section: Discussionsupporting
confidence: 83%
“…The anterior corpus callosum carried left and right ventral prefrontal cortex connections engaging in cognitive processing and emotional regulation 43 , 44 . Abnormalities in the corona radiata, which connects brainstem with prefrontal regions including the ventrolateral prefrontal cortex (VLPFC) and dorsolateral prefrontal cortex (DLPFC) 45 , 46 , are repeatedly reported in patients with BD 47 , 48 . This finding of increased FA in the WM might suggest signs of compensatory reactions to the subthreshold mood symptoms manifested in the bipolar offspring as we previously observed 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explication of the negative results of this follow-up study is that evidence indicates that in individuals at-risk for BD, WMA has been found in specifically brain regions (i.e. superior corona radiata (SCR)/corticospinal tract (CST) and the body of the corpus callosum) whereas changes in other WM tracts seem to be a disease state marker (Linke et al 2020 ).…”
Section: Imaging Endophenotypesmentioning
confidence: 96%
“…Regarding co-segregation of WMA with the genetic risk of BD, there is compelling evidence that are more frequent in URs compared to controls. Widespread FA reductions and significant lower FA values have been found in BD patients and their URs respect to healthy control subjects particularly in corpus callosum, the dorsal part of the right cingulum bundle, the hippocampal part of the cingulum bundle bilaterally, and the uncinate fasciculus (Sprooten et al 2013 , 2016 ; Mahapatra et al 2017 ; Linke et al 2020 ). Of note, a 2-year follow-up study identified similar trajectories of FA reductions for controls and high-risk young adults and failed to find differences in FA among URs of BD patients and healthy controls, suggesting that difference in WM integrity could occur in earlier childhood and be a necessary but not sufficient condition to develop future BD (Ganzola et al 2017 ).…”
Section: Imaging Endophenotypesmentioning
confidence: 99%